Influence of preoperative nucleus pulposus status and radiculopathy on outcomes in mono-segmental lumbar total disc replacement: Results from a nationwide registry - Zweig, T.; Hemmeler, C.; Aghayev, E.; Melloh, Markus; Etter, C.; Röder, C. (2011)
Background: Currently, herniated nucleus pulposus (HNP) with radiculopathy and other preconditions are regarded as relative or absolute contraindications for lumbar total disc replacement (TDR). In Switzerland it is left to the surgeon's discretion when to operate. The present study is based on the dataset of SWISSspine, a governmentally mandated health technology assessment registry. We hypothesized that preoperative nucleus pulposus status and presence or absence of radiculopathy has an influence on clinical outcomes in patients treated with mono-segmental lumbar TDR. Methods. Between March 2005 and April 2009, 416 patients underwent mono-segmental lumbar TDR, which was documented in a prospective observational multicenter mode. The data collection consisted of perioperative and follow-up data (physician based) and clinical outcomes (NASS, EQ-5D). Patients were divided into four groups according to their preoperative status: 1) group degenerative disc disease ("DDD"): 160 patients without HNP and no radiculopathy, classic precondition for TDR; 2) group "HNP-No radiculopathy": 68 patients with HNP but without radiculopathy; 3) group "Stenosis": 73 patients without HNP but with radiculopathy, and 4) group "HNP-Radiculopathy": 132 patients with HNP and radiculopathy. The groups were compared regarding preoperative patient characteristics and pre- and postoperative VAS and EQ-5D scores using general linear modeling. Results: Demographics in all four groups were comparable. Regarding the improvement of quality of life (EQ-5D) there were no differences across the four groups. For the two main groups DDD and HNP-Radiculopathy no differences were found in the adjusted postoperative back- and leg pain alleviation levels, in the stenosis group back- and leg pain relief were lower. Conclusions: Despite higher preoperative leg pain levels, outcomes in lumbar TDR patients with HNP and radiculopathy were similar to outcomes in patients with the classic indication; this because patients with higher preoperative leg pain levels benefit from a relatively greater leg pain alleviation. The group with absence of HNP but presence of radiculopathy showed considerably less benefits from the operation, which is probably related to ongoing degenerative processes of the posterior segmental structures. This observational multicenter study suggests that the diagnoses HNP and radiculopathy, combined or alone, may not have to be considered as absolute or relative contraindications for mono-segmental lumbar TDR anymore, whereas patients without HNP but with radiculopathy seem to be suboptimal candidates for the procedure. © 2011 Zweig et al; licensee BioMed Central Ltd.